Correlates of type and quantity of child communication during pediatric subspecialty encounters. Issue 11 (November 2015) - Vigilante, Vanessa Ann; Hossain, Jobayer; Wysocki, Tim; Sharif, Iman
Highlights We videotaped pediatric subspecialty visits and coded the child-provider communication. Child utterances accounted for 15% of all utterances during the encounters. Children in obesity clinic talked more. Efforts to teach motivational interviewing skills to providers in clinics other than obesity may increase child communication.